Alkaline pretreatment and the synergic effect of water and tetralin enhances the liquefaction efficiency of bagasse. (February 2015) - Li, Zhixia; Cao, Jiangfei; Huang, Kai; Hong, Yaming; Li, Cunlong; Zhou, Xinxin; Xie, Ning; Lai, Fang; Shen, Fang; Chen, Congjin
Highlights: Sugarcane bagasse was liquefied in a water/tetralin mixed solvent. The mixed solvent showed significantly synergic effect on bagasse liquefaction. The compositions of heavy oil obtained in different solvents are quite different. Alkaline pretreatment enhanced bagasse liquefaction in water-containing solution. Abstract: Bagasse liquefaction (BL) in water, tetralin, and water/tetralin mixed solvents (WTMS) was investigated, and effects of tetralin content in WTMS, temperature, and alkaline pretreatment of bagasse on liquefaction efficiency were studied. At 300 °C, bagasse conversion in WTMS with tetralin content higher than 50 wt% was 86–87 wt%, whereas bagasse conversion in water or tetralin was 67 wt% or 84 wt%, respectively. Because the solid conversion from liquefaction in WTMS with tetralin content higher than 50 wt% was always higher than that in water or tetralin at temperatures between 250 and 300 °C, a synergic effect between water and tetralin is suggested. Alkaline pretreatment of bagasse resulted in significantly higher conversion and heavy oil yield from BL in water or WTMS. The effect of deoxygenation by the present liquefaction method is demonstrated by lower oxygen contents (16.01–19.59 wt%) and higher heating values (31.9–34.8 MJ/kg) in the produced oils.